Residu Pestisida Organofosfat Pada Beras dan Perilaku Petani dalam Penggunaan Pestisida di Kabupaten Subang, Jawa Barat - Harisman, Muhammad Ikhsan; Abidin, Zaenal; Guntoro, Dwi (Jurnal Penelitian Pertanian Tanaman Pangan, 2021)
Organophosphate pesticides are widely used in agriculture asthey are the most toxic insecticides against vertebrates and easily biodegradable in nature. The objective of this study was to determine the organophosphate residue in rice from several rice varieties and behaviors of farmers in using pesticides. The study was conducted in Subang Regency, West Java, from May to June 2020 using a gas chromatography analysis method. The rice samples came from three sub-districts of Subang Regency, namely Ciasem, Purwadadi, and Sagalaherang in Subang Regency. The data collection of farmer behavior in the used of pesticides in rice farming were conducted by purposive sampling using questionnaires and interviews. The results showed that the residual contents of the organophosphate active ingredients(diazinon, chlorpyrifos, and fenitrotion) in Ciherang, Inpari-32 HDB, and IR64 rice varietes were significantly lower than the Maximum Residue Limits (BMR) of each pesticides allowed in agriculture based on the Indonesian National Standard (SNI) 7313: 2008, so it is safe for consumption. The low residue of organophosphate pesticides is related to the behavior of farmers in using pesticides which generally refers to recommendations and most farmers use pesticides according to the concept of integrated pest control, namely the right dose, right time, right type, and right target according to the type of pests and plant diseases.